Application Of Stimuli Program To Improve Literation Capabilities In Early Childhood - Nofha Rina; Lucy Pujasari Supratman; Abdul Fadli K (Lingkar Studi Komunikasi (LISKI), 2020)
Stimuli program is a program by providing a literacy book package containing instructions on activities, media literacy for children and socialization for mothers. Providing simulations to children must be in accordance with the characteristics of children by presenting learning activities that are fun. When doing stimuli, methods and media are important factors to do fun a ctivities. The results of this study apply a stimuli program for children at home through methods and media that are appropriate to the child's characteristics. This is done in the stimuli program by providing a literacy package consisting of instructions for activities, media literacy, and socialization for parents. The aim of the study was to examine the effectiveness of stimuli programs in improving literacy skills in early childhood. The proposed hypothesis is a stimuli program in increasing the ability of media literacy in early childhood. The method used is a quasi experiment with a non-equivalent control group design. The research subjects were 30 children aged four to five years who were divided into experimental and control groups. Based on the resu lts of the analysis through the non-parametric Mann - Whitney U statistical test, it was found that there were differences in the increase in the ability of media literacy in the experimental group with the control group. The qualitative analysis shows the results of an increase in literacy ability by observing changes in measurement results. The results of this study are important as new studies in finding alternative methods of early childhood stimuli. Keywords:stimuli, literacy, media, early childhood